Tuberculosis biomarkers: from diagnosis to protection - Delia Goletti; Elisa Petruccioli; Simone A. Joosten; Tom H.M. Ottenhoff (MDPI AG, 2016)
New approaches to control tuberculosis (TB) worldwide are needed. In particular, new tools for diagnosis and new biomarkers are required to evaluate both pathogen and host key elements of the response to infection. Non-sputum based diagnostic tests, biomarkers predictive of adequate responsiveness to treatment, and biomarkers of risk of developing active TB disease are major goals. Here, we review the current state of the field. Although reports on new candidate biomarkers are numerous, validation and independent confirmation are rare. Efforts are needed to reduce the gap between the exploratory up-stream identification of candidate biomarkers, and the validation of biomarkers against clear clinical endpoints in different populations. This will need a major commitment from both scientists and funding bodies.